(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The occurrence of cross-border adoptions presents intricate legal and ethical dilemmas, especially when considering the variations in national legislation and global norms. This dissertation, titled "Cross-Border Adoptions: An Investigation into Comparative Transnational Jurisprudence with Particular Emphasis on India," aims to analyse the issues associated with cross-border adoption cases by studying the approaches used by different legal systems, with a specific emphasis on India